Four weddings and a funeral - Grant, Hugh.; MacDowell, Andie; Newell, Mike, 1942-; PolyGram Filmed Entertainment (Firm); MGM Home Entertainment Inc.; Channel Four Films (Firm) (Santa Monica, CA : MGM Home Entertainment, 1999)
Romantic comedy about a young man who meets the girl of his dreams at a friend's wedding. However, she slips through his fingers when the timing seems wrong, and they meet at three more weddings and a funeral before the two finally connect.
DVD release of the 1993 motion picture.
Executive producers, Tim Bevan and Eric Fellner.
Hugh Grant, Andie MacDowell.
Rated R.
DVD.
Close-captioned for the hearing impaired.
Keywords: Feature films; Comedy films; Foreign language films; Films for the hearing impaired